PENGELOLAAN DANA BANTUAN OPERASIONAL SEKOLAH PADA SEKOLAH MENENGAH PERTAMA NEGERI 1 PARIGI KABUPATEN PARIGI MOUTONG - Rudin, Ahmad (Katalogis, 2015)
This research aims at describing the fund management of School Operational Assistance in Sekolah Menengah Pertama Negeri 1 Parigi, Parigi Moutong Regency. This research used descriptive qualitative method and the data collection techniques were observations, interviews, and documentations. Five informants were taken by using purposive sampling technique. The results shows that the fund management of School Operational Assistance at Sekolah Menengah Pertama Negeri 1 Parigi is not optimal, some aspects that were examined, for example the aspect of planning is good, the aspect of organization has been good, the aspect of scaling has been good, but the aspect of control is notgood.